Noonan Syndrome - Dina D.; Soetjiningsih Soetjiningsih; Hamid A.; Sudaryat S. (Paediatrica Indonesiana, 1994)
A case of Noonan syndrome in an Indonesian baby boy is reported. The diagnosis was based on history, physical examination and abnormalities on Denver Development Screening Test and Vineland Social Maturity Scale. Treatment consisted of hormonal therapy for cryptorchidism and short stature, physiotherapy, and surgical correction cryptorchidism and cardiac anomaly if necessary. The prognosis for life span was good.